PENGARUH UMUR PERUSAHAAN, LIKUIDITAS DAN PROFITABILITAS TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN “(TIMELINESS)” - Retna Sari (EQUITY, 2015)
This research was conducted to examine the effect age of company, likuidity and profitability to timeliness in the submission of the financial report of manufacturing in Indonesia Stock Exchange period 2012. Sample that as many as 92 companies. Sample determination technique using purposive sampling method. Hypotesis testing using a logistic anlysis. The result showed that all variables are not significantly to the timeliness.